Islam in Nineteenth-Century Wallo, Ethiopia : Revival, Reform and Reaction - Ahmed, Hussein (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
While presenting an historical account of the internal dynamics of Islam in Wallo, Ethiopia, with particular emphasis on the modes of its introduction and dissemination, and on its relationship with the Ethiopian state and regional power structure, this book describes the background to, and manifestations of, the revival and consolidation of Islam in the region in the nineteenth century by assessing the role of Muslim scholars, traders and chiefs in that process. It also traces the origin of the tradition of Islamic renewal and reform, and analyzes the response of Wallo Muslim religious intellectuals to the attempt of the Ethiopian Christian monarchs of the period to bring about the political unification of the kingdom by imposing a policy of religious coercion on the Muslims of Wallo. Based largely on hitherto-untapped oral and written indigenous sources, and supplemented by external archival and documentary evidence, the study is aimed at redressing the historiographical and interpretive imbalance embedded in the scholarly, institutional and popular perceptions on Islam in Ethiopia.